A revision of Delevea Reichardt, 1976: a Southern African endemic water beetle genus including the largest known extant myxophagans (Coleoptera: Myxophaga: Torridincolidae) - Bilton, David T.; Mlambo, Musa C. (Zootaxa, 2023)
The Southern African endemic torridincolid water beetle genus Delevea Reichardt, 1976 is revised, based largely on recently collected material from the Republic of South Africa. Significant range extensions are provided for the two previously described species, Delevea bertrandi Reichardt, 1976 and D. namibiensis Endrödy-Younga, 1997, these taxa apparently being endemic to the Fynbos Biome in the Western Cape Province and semi-arid, summer rainfall, areas of the Great Escarpment in Namibia and South Africa, respectively. In addition, two new species, Delevea madiba sp. nov. and D. namaqua sp. nov. are described from winter rainfall areas of Namaqualand in the Northern Cape Province. Both species are currently only known from their type locality and, at up to 2.85 mm in adult body length, D. namaqua sp. nov. is the largest described extant species of the suborder Myxophaga.